DATA PROCESSING APPLICATIONS COMMUNITY MEMBERS OIKUMENE STMIK JAKARTA STI & K by using Microsoft Visual FoxPro 9.0 - Arip Prihanto (Jurnal Sistem Informasi, 2007)
The growing world of computer technology so that all problems can be solved with a computer, one of which is to create an "Application for data processing", where with this application we can be easier and faster to process data. This application is designed with the view that attention to convenience and attractive design